Strategi green economic: pelatihan pemandu ekowisata mangrove di Kenagarian Sungai Pinang Kabupaten Pesisir Selatan - Wahyudin, Rama; Karina, Indira; Putra, Pandhu Rochman Suosa (Universitas Halu Oleo, 2023)
Utilizing opportunities that arise from the potential natural and cultural riches of the Nagari Sungai Pinang – Pesisir Selatan community has become an innovation for developing a Green Economy Strategy. This model is a projection that brings benefits to improving people's welfare while still paying attention to and making good use of the environment. This research is a type of qualitative descriptive research, using the PAR (Participatory Action Research) method. This research is a form of Community Service by providing literacy and outreach to community groups in the Andespin Community. The results of this research are in the form of utilizing the potential of Nagari Sungai Pinang to be developed into ecotourism, such as the formation of community groups that understand the meaning of Green Economics as a form of creating an environmentally friendly economic system, secondly the formation of micro business groups that utilize marine resources into processed products in the form of frozen food, as well as the concept of utilization environment as a good mangrove tourism.